2013
DOI: 10.5088/2013.35.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Marine Nematoda from Ajuruteua beach, Amazon Coast, Brazil

Abstract: RESUMOEste estudo objetiva preencher uma lacuna do conhecimento sobre nematodeos no Brasil, fornecendo a primeira lista de gêneros de uma praia arenosa amazônica brasileira (Ajuruteua, Pará). As amostras foram coletadas em junho de 2009 ao longo de quatro transectos perpendiculares à linha da praia ao longo do médio litoral (supra, médio e infra), usando um amostrador cilíndrico de 3.14 cm 2 , o qual foi enterrado até 10cm no sedimento. Um total de 17 famílias e 47 gêneros foi registrado. Entre as famílias Xya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
2
1
0
1
Order By: Relevance
“…Fonseca et al (2014) stated that Theristus showed a broad distribution that was correlated with average grain size. The high abundance of Daptonema in this study agrees with what has been previously reported indicating that this genus is commonly an abundant nematofaunal taxa present in various environments, especially in sandy beaches (Pereira-Gomes de Melo et al 2013) with well-selected sands (Moreno et al 2008) or fine sand (Corbisier et al 2008).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Fonseca et al (2014) stated that Theristus showed a broad distribution that was correlated with average grain size. The high abundance of Daptonema in this study agrees with what has been previously reported indicating that this genus is commonly an abundant nematofaunal taxa present in various environments, especially in sandy beaches (Pereira-Gomes de Melo et al 2013) with well-selected sands (Moreno et al 2008) or fine sand (Corbisier et al 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Four trophic types were identified in both sampling periods, although selective deposit feeders constituted less than 2% of the meiofaunal community. In contrast, nonselective deposit feeders dominated the community followed by epistrate feeders, which agrees with what was reported by Pereira-Gomes de Melo et al (2013). The high representativeness of nonselective deposit feeders on Gaibu Beach agrees with what was reported by Alongi (1990), who stated that this group is dominant during warm months due to the elevated number of bacteria, protozoa, and microphytobenthos present.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations